The Effect of ROE on the PBV of Toll Road, Airport, Port, and Sub-Sector Companies in the Indonesia Stock Exchange - Andy; SH, Hengky (Journal of Management Research, 2024)
This research has been conducting before and during the Covid 19 pandemic and aims to test the effect of the Return on Equity (ROE) to the Price Book Value (PBV) of toll road subsector’s companies, airports, and the like on the Indonesian Stock Exchange (ISE) for 6 years in Indonesia. This type of research uses quantitative research and is equipped with verification with an explanatory survey method. The sampling method used a purposive. It took from five sample companies. Data analysis in this study used panel data regression with the results: The results of this study indicate that ROE has a strong effect on firm value.